PEMBELAJARAN IPA BERBASIS ETNOSAINS DALAM TINJAUAN FILSAFAT - Nadia Kurnia Ningsih; Muhammad Nurwahidin; Sudjarwo Sudjarwo (Bajang Institute, 2022)
Ethnoscience is a learning that describes cultural values ​​(original science) as a form of natural phenomena that grow in the community and the truth can be studied empirically. Ethnoscience raises local wisdom and cultural understanding as objects of study in science learning which will then be scientifically tested into science learning in schools. The purpose of this study is to examine philosophy in the aspects of ontology, epistemology, and axiology of ethnoscience studies in science learning. This study uses the